The ethology of empathy: a taxonomy of real-world targets of need and their effect on observers - Preston, Stephanie D.; Hofelich, Alicia J.; Stansfield, Robert B. (Frontiers in Human Neuroscience, 2013)
Empathy is inherently interpersonal, but the majority of research has only examined observers. Targets of need have been largely held constant through hypothetical and fictionalized depictions of sympathetic distress and need. In the real world, people's response to life stressors varies widely—from stoicism to resilience to complete breakdown—variations that should profoundly influence the prosocial exchange. The current study examined naturally-varying affect in real hospital patients with serious chronic or terminal illness during videotaped interviews about quality of life. Participants viewed each video while psychophysiological data were recorded and then rated each patient's and their own emotion. Patients displayed three major emotion factors (disturbed, softhearted, and amused) that were used to classify them into five basic types (distraught, resilient, sanguine, reticent, wistful). These types elicited four major emotions in observers [personal distress (PD), empathic concern (EC), horror, pleasure], two of which were never discovered previously with fictionalized targets. Across studies and measures, distraught targets usually received the greatest aid, but approximately as many observers preferred the positive and likeable resilient patients or the quietly sad wistful targets, with multiple observers even giving their greatest aid to sanguine or reticent targets who did not display distress or need. Trait empathy motivated aid toward more emotive targets while perspective taking (PT) motivated aid for those who did not overtly display distress. A second study replicated key results without even providing the content of patients' speech. Through an ecological examination of real need we discovered variation and commonality in the emotional response to need that interacts strongly with the preferences of observers. Social interactions need to be studied in ethological contexts that retain the complex interplay between senders and receivers.